COGNITIVE AND SOCIAL OUTCOMES OF PROJECT-BASED LEARNING (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
A cognitive theory of learning sees second language acquisition as a conscious and reasoned thinking process, involving the deliberate use of learning strategies. However, a second/foreign language and content are best acquired when students use them in real-life situations. Project-based learning offers a chance to develop various cognitive skills regarded as professional qualities facilitating their re-integration in society. It also shows that socio-affective skills are developed during project-based learning. The successful acquisition of skills such as persistence, willingness, cooperativeness, creativity and initiative, according to the present work, depends on and is linked to each learner’s personal experiences, traits, needs, interests and objectives which during project-based learning are engaged but subordinated to social, cooperative objectives and expectations